))The impact of the creative drama strategy to develop the skills of students of the Institute of Fine Arts in school theater(( (Journal of the College of Basic Education, 2023)
The research problem was identified in the following question: What is the impact of the creative drama strategy on developing the skills of the students of the Institute of Fine Arts in the school theater subject.The current research aims to identify the impact of the creative drama strategy in developing the skills of the students of the Institute of Fine Arts in the school theater subject.The researcher reached the following results:1- Clearly increasing the skills of the experimental group itself gives a clear indication of the success of the strategy and has a clear impact.2- The steps of the creative drama strategy had a clear impact on developing the skills of the students of the theater department at the Institute of Fine Arts in the school theater subject.